Conformal oxide nanocoatings on electrodeposited 3D porous Ni films by atomic layer deposition. Issue 37 (17th August 2016) - Zhang, J.; Coll, M.; Puig, T.; Pellicer, E.; Sort, J.
Abstract : A versatile chemical synthesis procedure to obtain Al2 O3 and Co2 FeO4 nanolayers by conformally coating a three-dimensional (3D) porous Ni film is presented. Abstract : A versatile chemical synthesis procedure to obtain Al2 O3 and Co2 FeO4 nanolayers conformally coating a three-dimensional (3D) porous Ni film is presented. First, porous Ni is grown by hydrogen bubble template-assisted electrodeposition. Subsequently, Al2 O3 and Co2 FeO4 layers, with thickness ranging from 5 nm to 25 nm, are directly deposited onto the pore walls by atomic layer deposition, while maintaining the porous architecture and magnetic properties of the Ni scaffold. The crystal structure, thickness and distribution of elements within the composite coatings are investigated in detail. The resulting magnetic and wettability properties are assessed. Contact angle tests reveal that 3D porous Ni films become more hydrophilic after coating with Al2 O3 or Co2 FeO4 . From a technological point of view, the obtained composite porous films could be appealing for application in magnetically actuated micro/nano-electromechanical systems (MEMS/NEMS) or bio-MEMS/NEMS, among others.